Constraints of Parents in Accompanying Children in Distance Learning (PJJ) in Bungursari Village - Viona; Imam Tabroni; Ayit Irpani (Acta Psychologia, 2022)
At present, Indonesia does not seem to be completely free from the Covid-19 emergency. This can be seen from the number of schools that implement distance learning (PJJ) to prevent the transmission of the virus. However, the implementation of this PJJ seems to have various obstacles from the perspective of parents, teachers, and students. The purpose of this research is to find out the obstacles of parents in accompanying their children in distance learning in the village. Researchers used qualitative methods with data obtained through the distribution of questionnaires. The results showed that some of the obstacles experienced by parents include difficult learning methods, technology limitations, difficult children to manage, and time constraints.